THE ANALOGY BETWEEN VERBUM DEI INCARTUM AND VERBUM DEI SCRIPTUM IN THE FATHERS - Crehan, J. H. (The journal of theological studies, 1955)
J. H. CREHAN, S.J.; THE ANALOGY BETWEEN VERBUM DEI INCARTUM AND VERBUM DEI SCRIPTUM IN THE FATHERS, The Journal of Theological Studies, Volume VI, Issue 1, 1 Ap